A pyrazole-based thioxanthone photoinitiator - Dogruyol, Sevnur Keskin; Kocatepe, Suhedanur (Lukasiewicz Research Network-Industrial Chemistry Inst, 2026)
9-(2-(1H-pyrazol-1-yl) acetyl)-12H-benzo[b]thioxanthen-12-one (TXMPPY) was synthesized by using 1-(naphthalen-2-yl)-2-(1H-pyrazol-1-yl) ethanone (MPPY) photoinitiator as starting material. Structure of TXMPPY was characterized by UV-Vis, FT-IR and 1H-NMR spectral analysis. The polymer-ization of TXMPPY with methyl methacrylate (MMA) monomer was studied at different concentrations in air and nitrogen atmospheres, both in the presence and absence of triethylamine (TEA), a tertiary amine. The photo physical properties of the photoinitiator and the changes in electronic transitions due to its solvent effect were elucidated using the UV-Vis spectrophotometry method. The time-resolved spectrofluorometer was employed to record fluorescence emission and decay profiles, allowing the de-termination of fluorescence lifetime. According to results, hydrogen abstraction process is dominant path for the formation of initiating radicals.
Keywords: photopolymerization; photoinitiator; thioxanthone; pyrazole; antibacterial; FREE-RADICAL POLYMERIZATION; LIGHT; SYSTEMS; DERIVATIVES; COATINGS; ACID; Polymer Science